2020
DOI: 10.3390/ani10071208
|View full text |Cite
|
Sign up to set email alerts
|

Use of GnRH for Synchronization of the Follicular Wave in Assisted Reproductive Technologies in Sheep: A Preliminary Study

Abstract: The present study aimed to set up a short-term protocol for synchronization of follicular wave emergence in sheep, concomitant with estrus synchronization, which would improve ovarian response in assisted reproductive technologies. Administration of a single GnRH dose, concomitant with the insertion of a progesterone-loaded CIDR device, caused regression of gonadotrophin-dependent follicles ≥4 mm in all the GnRH-treated sheep and in around 80% of the controls treated only with CIDR (p < 0.05). Similar perce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 32 publications
(35 reference statements)
0
7
1
1
Order By: Relevance
“…Here we dare ourselves that GnRH is less efficient if it turns out that T1 compared to T2 seems to be no significant difference. Another reason that hormones stimulate the release of gonadotropins (GnRH) is a key neuro-peptide that controls the reproductive function of vertebrates, especially in ewe expected to experience spontaneous ovulation, ovarian steroids released by mature ovarian follicles controlling pulsatile patterns of GnRH release from the hypothalamus, in turn, stimulates the preovulatory secretions of the luteinizing hormone (LH) by the anterior pituitary gland 17 .…”
Section: Resultsmentioning
confidence: 99%
“…Here we dare ourselves that GnRH is less efficient if it turns out that T1 compared to T2 seems to be no significant difference. Another reason that hormones stimulate the release of gonadotropins (GnRH) is a key neuro-peptide that controls the reproductive function of vertebrates, especially in ewe expected to experience spontaneous ovulation, ovarian steroids released by mature ovarian follicles controlling pulsatile patterns of GnRH release from the hypothalamus, in turn, stimulates the preovulatory secretions of the luteinizing hormone (LH) by the anterior pituitary gland 17 .…”
Section: Resultsmentioning
confidence: 99%
“…This could also be a reason why most of the studies have focused on the manipulation of the first wave, which emerges on the ovulation day of the previous cycle, as it is very difficult to predict when other waves would emerge (6,8). Therefore, our study, as in researchers' studies, has been designed to regress large follicles on the ovaries with the insertion of intravaginal devices containing progesterone or its analogues, thus creating a new follicle wave after the withdrawal of intravaginal devices (Day 0 Protocol) (8,20). Also, it has been reported that a new wave of follicles does not emerge unless the large follicles on the ovaries regress (5,8,21).…”
Section: Discussionmentioning
confidence: 99%
“…Also, it has been reported that a new wave of follicles does not emerge unless the large follicles on the ovaries regress (5,8,21). In a previous study, Año-Perello et al (20) reported that 81.1% (30/37) of large follicles regressed 24 h after insertion of a controlled internal drug releasing device (CIDR) in Segureña meat ewes, and plasma E2 concentrations decreased significantly between days 0 and 1. Despite using the same synchronization protocol in our study, no change in serum E2 concentrations was observed between days 0 and 1 in the control group.…”
Section: Discussionmentioning
confidence: 99%
“…However, commonly used methods are estrous‐focused methods, and follicular development is less prominent. In applications such as fixed‐time insemination or MOET, follicular development‐focused methods are used (Año‐Perello et al., 2020). In these methods, it is essential to know the number of follicles developed, the certain time when follicular waves commence or the time of ovulation.…”
Section: Introductionmentioning
confidence: 99%